Neighbor love through fearful days : finding purpose and meaning in a time of crisis - Mahn, Jason A., 1973- (Fortress Press, 2021)
Neighbor Love through Fearful Days is a reflection on the Covid-19 pandemic, the accompanying economic collapse, a summer of climate chaos, and the pandemic of white supremacy, as well as on the calling to ""serve thy neighbor"" and work toward the common good. Jason A. Mahn's real-time reflections take on the reality of life during these pandemics alongside perennial questions about purpose, faith, and vocation